53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-1602
|View full text |Cite
|
Sign up to set email alerts
|

Physics of Heat-Release in Rotating Detonation Engines

Abstract: Rotating detonation engines (RDEs), along with the well-studied Pulsed Detonation Engine (PDEs), represent an alternative for obtaining propulsion and power generation using the high efficiency detonation cycle. In the last half decade, the RDE has been studied aggressively internationally due to its advantages over conventional PDEs. Many previous studies have focused on the main characteristics and performance of RDEs in various configurations and conditions. The performance of any combustor is tied closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The comparison between premixed and non-premixed cases, as in [113], shows that the number of waves and location of the detonation wave are different for premixed and non-premixed case. Schwer et al [114] investigated the distribution of heat release in an RDE with the variation in different critical parameters such as air/fuel injection pressure, injector size and mixing ratios. The fluid particle trajectory is studied by Zhou et al [115], and has reported that while the deflagration wave doesn't deflect the particle, the detonation wave or oblique shock changes the flow parameters rapidly.…”
Section: Fuel Flexibility Of Rdes Using Numerical Methodsmentioning
confidence: 99%
“…The comparison between premixed and non-premixed cases, as in [113], shows that the number of waves and location of the detonation wave are different for premixed and non-premixed case. Schwer et al [114] investigated the distribution of heat release in an RDE with the variation in different critical parameters such as air/fuel injection pressure, injector size and mixing ratios. The fluid particle trajectory is studied by Zhou et al [115], and has reported that while the deflagration wave doesn't deflect the particle, the detonation wave or oblique shock changes the flow parameters rapidly.…”
Section: Fuel Flexibility Of Rdes Using Numerical Methodsmentioning
confidence: 99%
“…There may be one or several rotating detonation waves (RDWs) moving tangentially in the RDE combustor [7]. Chemical reactions mainly occur inside the detonation wave, although there may still be deflagrative combustion near the walls [8] or between the reactants and products [9]. The rotating propagation and pressure-gain combustion together make the detonation wave continuous.…”
Section: Introductionmentioning
confidence: 99%